2008
DOI: 10.1007/s00018-008-7550-3
|View full text |Cite
|
Sign up to set email alerts
|

Cbln and C1q family proteins – New transneuronal cytokines

Abstract: The C1q family is characterized by a C-terminal conserved global C1q domain, which is structurally very similar to the tumor necrosis factor homology domain. Although some C1q family members are expressed in the central nervous system, their functions have not been well characterized. Cbln1, a member of the Cbln subfamily of the C1q family, is predominantly expressed in cerebellar granule cells. Interestingly, Cbln1 was recently shown to play two unique roles at excitatory synapses formed between cerebellar gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 44 publications
1
61
0
Order By: Relevance
“…Further studies are warranted to clarify the role of Cbln1 in the regulation of activity-dependent structural plasticity in adult wild-type cerebellum. Since the Cbln family (Cbln1-Cbln4) and other C1q/ TNF␣ superfamily members are expressed in various regions of the mature brain (Yuzaki, 2008), understanding the role of Cbln1 will be of great benefit for unraveling various forms of synaptic plasticity in the adult brain.…”
Section: Physiological Role Of Activity-induced Downregulation Of Cbln1mentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are warranted to clarify the role of Cbln1 in the regulation of activity-dependent structural plasticity in adult wild-type cerebellum. Since the Cbln family (Cbln1-Cbln4) and other C1q/ TNF␣ superfamily members are expressed in various regions of the mature brain (Yuzaki, 2008), understanding the role of Cbln1 will be of great benefit for unraveling various forms of synaptic plasticity in the adult brain.…”
Section: Physiological Role Of Activity-induced Downregulation Of Cbln1mentioning
confidence: 99%
“…Cbln1 belongs to a Cbln subfamily (consisting of Cbln1-Cbln4) of the C1q/tumor necrosis factor (TNF) superfamily (Yuzaki, 2008). In the cerebellum, Cbln1 is released from granule cells and plays a crucial role in forming excitatory synapses between parallel fibers (PFs; axons of granule cells) and Purkinje cells during development; the number of PFPurkinje cell synapses decreased by 80% in mice with a disrupted cbln1 gene (cbln1 Ϫ/Ϫ ) (Hirai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins of this superfamily, among others are involved in the classical pathway of complement activation, host defense, inflammation, apoptosis, autoimmunity, cell differentiation, organogenesis, hibernation, and insulin-resistant obesity (1). The subfamily of Cbln, on the other hand, is highly expressed in various regions of the brain and recent data suggest they belong to a new class of transneuronal regulators of synapse development and synaptic plasticity (2).…”
Section: Introductionmentioning
confidence: 99%
“…Cbln3 binds specifically to Cbln1 (6) and recently Cbln4 was identified (7) (NCBI accession number NM_175631). All members of the Cbln family form homomeric and also heteromeric complexes with each other in vitro and it was suggested that such complexes play a crucial role in normal development of the cerebellum (2,8). However, not only entire Cbln molecules are able to act as a transneuronal cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in molecular biology methods has allowed identification of the entire subfamily of precerebellins (Cblns), which comprises four propeptides named Cbln1-4 (2-6). Cbln-related genes are located at different chromosomes, and Cblnencoded proteins are highly conserved (4,7,8). All of them are highly expressed in the central nervous system, particularly in the cerebellum.…”
Section: Introductionmentioning
confidence: 99%